Assessment of the Epidemic Process of COVID-19 Manifestations and the Epidemiological Efficacy of the Vaccine Gam-Covid-Vac Among Employees of a Multi-Speciality Medical Organization - V. I. Sergevnin; S. M. Ratnikova; N. G. Zueva; M. V. Rozhkova (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. Employees of medical organizations (MO), by virtue of their official duties, are at the group risk of morbidity of a new coronavirus infection.Aim. Evaluation of the manifestations of the COVID-19 epidemic process and the epidemiological effectiveness of the use of the Gam-Covid-Vac vaccine among employees of a multy-speciality medical organization.Materials and methods. The incidence of COVID-19 among the staff of MO was studied for the period from March 2020 to December 2021. The latent epidemic process was evaluated avccording to the results of routine serological examination of employees for antibodies of classes IgM and IgG to SARS-CoV-2. The epidemiological effectiveness of immunoprevention was determined by comparing the incidence with the coverage of employees who has a completed course of vaccination.Results. During the study period, 47.7% of employees of medical organizations had a clinically apparent form of COVID-19. In addition, according to the results of a routine serological examination, it turned out that 46.5% of employees had a subclinical form of infection. An increased level of morbidity was observed in the autumn period. The incidence of medical workers was in 2.2 times higher than other employees, medical staff of the hospital – in 1.7 times higher than polyclinics. The epidemic process was more intense in the group of nurses than doctors and junior medical staff. The epidemiological efficacy of the Gam-Covid-Vac during the first months of using vaccine has been established. Vaccinated people have a more mild course of COVID-19 in comparison with unvaccinated people.Conclusion. In this way, the main manifestations of the COVID-19 epidemic process in employees of a multy-speciality medical organization were identified and the epidemiological effectiveness of the Gam-Covid-Vac vaccine in the first months of using vaccine was established